Synthesis and Application of Albumin Nanoparticles Loaded with Prussian Blue Nanozymes - Pavel Khramtsov; Maria Kropaneva; Maria Bochkova; Valeria Timganova; Dmitriy Kiselkov; Svetlana Zamorina; Mikhail Rayev (Colloids and Interfaces, 2022)
Prussian blue nanozymes exhibit peroxidase-like catalytic activity and are therefore considered a stable and inexpensive alternative to natural peroxidases in the enzyme-linked immunosorbent assay (ELISA). In this work, we propose a robust method of Prussian blue nanozyme functionalization, which relies on the entrapment of nanozymes into albumin nanoparticles. The principle of the method is the addition of ethanol to a solution that contains albumin and nanozymes. At a high ethanol concentration solubility of albumin decreases, resulting in the formation of albumin nanoparticles loaded with nanozymes. The hydrodynamic diameter of nanoparticles was between 120 and 230 nm and depended on the nanozyme-to-BSA ratio. Encapsulation efficiency of nanozymes reached 96–99% and up to 190 μg of nanozymes were loaded per 1 mg of nanoparticles. Nanoparticles were stable at pH 5.5–7.5 and upon long-term storage in deionized water. Excellent reproducibility of the synthesis procedure was confirmed by the preparation of three individual batches of Prussian-blue-loaded BSA nanoparticles with almost identical properties. Nanoparticles were functionalized with monoclonal antibodies using glutaraldehyde cross-linking. The resulting conjugates were applied as labels in an ELISA-like assay of tumor marker prostate-specific antigen (PSA). The lower limit of detection was below 1 ng/mL, which enables measurement of PSA in the range of clinically relevant concentrations.